Of Monsters, Myths and Marketing: The Case of the Loch Ness Monster - Moir, James (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2015)
This paper examines the status of the Loch Ness Monster within a diverse body of literature relating to Scotland. Within cryptozoology this creature is considered as a source of investigation, something to be taken seriously as a scientific or quasi-scientific object to be studied and known, particularly in light of its elusive nature. In terms of mythology the creature is bound up with Scottish cultural identifications through references to a rugged wilderness landscape and to iconic, if stereotypical, images of tartanry, bygone castles, and folklore. Both sets of ideas have been used with great effect to generate a diversity of literature: from books and scientific papers that chronicle the sightings and “hunt” for the creature as well the possible case for it being a line of long-surviving plesiosaurs, through to children’s literature that deals with the mythic element that is so often used to appeal to childhood imagination, and on to a plethora of tourist marketing booklets and brochures.